2022
DOI: 10.1186/s12936-022-04274-8
|View full text |Cite
|
Sign up to set email alerts
|

Anopheline diversity in urban and peri-urban malaria foci: comparison between alternative traps and seasonal effects in a city in the Western Brazilian Amazon

Abstract: Background Continuous vector surveillance and sustainable interventions are mandatory in order to prevent anopheline proliferation (or spread to new areas) and interrupt malaria transmission. Anopheline abundance and richness were evaluated in urban and peri-urban malaria foci at a medium-sized city in the Brazilian Amazon, comparing the protected human landing catch technique (PHLC) and alternative sampling methods over different seasonal periods. Additional information was assessed for female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(131 reference statements)
1
0
0
Order By: Relevance
“…However, at high densities, it can behave as an opportunistic species, and depending on the availability of vertebrate hosts, it can play a role in malaria transmission. In the present study, these species showed attractiveness to humans, as observed in other studies 29 , 30 . The evidence that those two species can bite humans in addition to the susceptibility to P. vivax and the capacity to develop sporozoites indicates that they must be important for maintenance of malaria transmission cycles.…”
Section: Discussionsupporting
confidence: 92%
“…However, at high densities, it can behave as an opportunistic species, and depending on the availability of vertebrate hosts, it can play a role in malaria transmission. In the present study, these species showed attractiveness to humans, as observed in other studies 29 , 30 . The evidence that those two species can bite humans in addition to the susceptibility to P. vivax and the capacity to develop sporozoites indicates that they must be important for maintenance of malaria transmission cycles.…”
Section: Discussionsupporting
confidence: 92%